Perceived self-efficacy and future expectations of rural, low-qualified NEET youths in a small peripheral region of Portugal - Lima, Amanda Nunes de Almeida (2019)
Our study intended to explore how socioeconomic status (SES) indicators and perceived self-efficacy perceptions are associated with future expectations, namely professional and community involvement expectations among rural, underqualified youths Not in Employment, nor in Education or Training (NEET), and if this model varies across gender groups. One-hundred and eighty eight NEET youths aged 18 to 29 years old participated in this study. One-hundred and two of them (54.30%) were aged between 18 and 24 years old, the majority were female (58.50%) and 65.40 % had completed upper middle school (9th grade) or less. Our data collection took place in the Azores islands, a small and peripheral Portuguese archipelago, with the support of the local employment agency. Using a Structural Equation Model approach, we found that participants showing more positive perceptions regarding their self-efficacy strengths showed stronger expectations regarding their professional future, contrary to those who perceived their self-efficacy as a barrier. We also found that greater independence regarding parents’ household as well as more positive perspective about self-efficacy resources showed to increment these women’s sense of self-efficacy compared to men.